Data collaboration in digital government research: A literature review and research agenda - Schmeling, Juliane; al Dakruni, Sami; Mergel, Ines (Elsevier, 2025)
Sovereign data infrastructures are a central building block of the European Data Strategy, yet little is known about how public administrations share and collaborate on both open and restricted data. This research addresses the gap by systematically analysing the existing literature on data collaboration within the field of digital government research. We thereby make a methodological contribution to digital government research through a rigorous literature review framework that includes Structural Topic Modelling to understand the different themes of the scientific discussion in the field of digital government. We propose an innovative data collaboration framework that includes the ecosystem, the organisational, and the individual levels, enhancing our understanding of the multidimensional nature of data collaboration. Our analysis reveals that while the emphasis is on innovation and participation, critical aspects like standardisation and data management have a declining topic prevalence, despite their importance in developing federated data ecosystems. This comprehensive analysis not only sheds light on the current landscape but also informs a structured research agenda in digital government, aiming to contribute to the advancement of the field.
Keywords: Data collaboration; Data ecosystem; Data space; Computational literature review; Structural topic modelling; Digital government; Public Management; Julkisjohtaminen